PENGARUH NON PERFORMING LOAN (NPL) DAN NET INTEREST MARGIN (NIM) OF LOAN TERHADAP DEPOSIT RATIO (LDR) PADA BANK RAKYAT INDONESIA TBK. PERIOD 2007-2014 - Windi Novianti; Noer Dwi Purnama Rini (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
This study was conducted to examine the effect of non-performing loan (NPL) and Net Interest Margin (NIM) of the Loan to Deposit Ratio (LDR). The object of this study is Bank Rakyat Indonesia Tbk. by using the Financial Report 2007- 2014 period. The method used in this research is descriptive method verification. The data used in this study is the quarterly financial statements published by the People Indonesia Stock Exchange 2007-2014 period through the site bri.co.id. For processing such data, in this study used statistical analysis classical assumptions (Normality, Multicollinearity, Heteroskidastity, and autocorrelation), a simple linear analysis, multiple regression analysis, correlation coefficient analysis, analysis coefficient of determination, whereas hypothesis testing used was t test and F test During the observation period of the study showed that the data were normally distributed. Based normality test, multicollinearity, heteroscedasticity test and autocorrelation test found no variables that deviate from the classical assumption. This shows the available data has been qualified using multiple linear regression model.The res ults showed that the NPL variable has no significant effect on LDR. NIM significant effect on the LDR. Predictive ability of both variables on LDR in this study amounted to 42.2%, while the remaining 57.8% is affected by other factors not examined. Keywords: Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Net Interest Margin (NIM).